Evaluation of wastewater treatment inside a watershed with water quality mathematical model – Case study of the Muqui do Norte river watershed (Espírito Santo, Brazil) (Research, Society and Development, 2021)
The main purpose of this work was to evaluate, with a mathematical model of water quality, the perspectives of wastewater treatment in the Muqui do Norte river watershed (Espírito Santo, Brasil). The QUAL-UFMG model was used to model the watercourses in the study area. The physiographic characterization, evaluation of water availability and the conditions of production and treatment of wastewater in Muqui do Norte river watershed preceded the water quality modeling. Two scenarios for disposal of effluents were modeled: a) final disposal of raw sewage; b) final disposal of effluents with treatment provided for in the municipal sanitation plans for the cities of Muqui and Atílio Vivácqua. The results indicated that the quality standards for Dissolved Oxygen and Biochemical Oxygen Demand are not met along in the Muqui River, considering the final disposal of raw sewage. They also indicated that the adoption of treatments suggested by the municipal sanitation plans of Muqui and Atílio Vivácqua would not allow to respect the OD standard in the last five kilometers of the simulated stretch. To attend the standard for OD in the Muqui do Norte River, the BOD efficiency removal at the stations in the municipality of Atílio Vivácqua must be raised to a minimum of 70%.